The Relationship Among the Inflation, Broad Money and Economic Growth: Evidence from Nepal (The Lumbini Journal of Business and Economics, 2021)
This paper intends to study the relationship among the inflation, broad money (M2) and economic growth during 2031-2075B.S. by using time series econometric tools. The stationary of all variable have been examined to determine the order of integration, for this ADF test has been applied. Variables are found to be stationary at level (0) and first I(1) difference. Johnsen Co-integration and vector error correction model (VECM) have been applied to show the relation among the variables and residuals diagnostic tools (serial LM test, Heteroscedasticity test and normal distribution test) have also tested to make estimation free of spurious. The study has shown there is long run association among inflation, broad money and economic growth in Nepal.